Predictors of diarrhea episodes and treatment-seeking behavior in under-five children: a longitudinal study from rural communities in Zambia - Hamooya, Benson Malambo (Pan Afr Med J, 2020)
INTRODUCTION: globally, diarrhea is the second leading cause of mortality in children aged below five years, and is responsible for killing about 760 000 children every year. Poor treatment-seeking behavior among caretakers remains a major challenge in low-income countries. The current study aimed to determine the predictors of diarrhea episodes and treatment-seeking behavior among under-five children of Chivuna and Magoye in Zambia. METHODS: we conducted a community-based longitudinal study among 1216 children aged 12-59 months between July 2006 and June 2007. A structured interviewer-administered questionnaire was used to collect data on demographic factors, diarrhea episodes and treatment-seeking behavior from caretakers. Chi-square, one-sample test of proportions and logistic regression were the statistical methods used in this study. RESULTS: of the 1216 children who participated in the study, 698 (57%) were from Chivuna and 518 (43%) from Magoye. Factors associated with diarrhea episodes were location (children in Chivuna had increased episodes of diarrhea; aOR 1.32; 95%CI 1.15, 1.52) and age distribution (children aged 37-59 months vs. 12-36 months had reduced episodes of diarrheal aOR 0.81; 95%CI 0.72, 0.91). Fifty two percent (52%) of the diarrhea cases had their treatment sought within 24 hours of onset (early treatment). Thirty one percent (31%) of the diarrhea cases had their early treatment at a health facility. Female children (52%) had the majority of their diarrhea episodes treated within 24 hours of onset. The higher proportion of diarrhea episodes had their treatment at home (52%). Children who did not have home treatment had a significantly reduced chance of having early treatment (aOR 0.62; 95%CI 0.47, 0.82). CONCLUSION: this study revealed that diarrhea episodes and treatment seeking behavior in under-5 children is of public health concern. There is need to re-enforce the preventative and control measures aimed at reducing diarrhea in under-5 children, and interventions should take into account the different predictors of diarrhea and treatment seeking behavior in different settings, like the ones highlighted in this study.